PEMIKIRAN PENDIDIKAN MUHAMMAD ABDUH DAN KONTRIBUSINYA TERHADAP PENGEMBANGAN TEORI PENDIDIKAN ISLAM - Falasipatul Asifa (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2018)
Abstract Muhammad abduh was a reformer figure at century 19’th that the ideas were very shining to renewal of Islam from various aspects. Abduh could resurrect the fighting spirit of Muslims to advanced in Scientist after had period of stagnation. Muhammad Abduh started repaire trough education. Make education as key sectors to saved the Mesir people.Making educational improvements as a principle in scoring sholeh Muslims. Education Muhammad Abduh aims to educate mind and soul and develop it to the extent the enables students to achieves happiness in the world and the hereafter. As for its connection with the curriculum Muhammad Abduh seems to want an integral Islamic Education was integral at each level of education in accordance with the purpose of education. while to overcome the weakness of educational methods that occurred at that time, Muhammad Abduh applied varied methods. Abstrak Muhammad Abduh adalah sosok pembaharu pada abad 19 yang ide-idenya sangat cemerlang untuk pembaharuan Islam dari berbagai aspek. Abduh bisa membangkitkan kembali semangat juang umat Islam untuk terus maju dalam bidang ilmu pengetahuan setelah mengalami fase kejumudan. Muhammad Abduh memulai perbaikannya melalui pendidikan. Menjadikan pendidikan sebagai sector utama guna menyelamatkan masyarakat Mesir. Menjadikan perbaikan pendidikan sebagai asas dalam mencetak muslim yang sholeh. Pendidikan Muhammad Abduh bertujuan mendidikan akal dan jiwa serta mengembangkannya hingga batas-batas yang memungkinkan anak didik mencapai kebahagiaan hidup di dunia dan di akhirat. Adapun kaitannya dengan kurikulum Muhammad Abduh tampak menginginkan kurikulum pendidikan islam yang integral pada setiap jenjang pendidikan sesuai dengan tujuan pendidikannya. Sedangkan untuk mengatasi kelemahan metode pendidikan yang terjadi pada masa itu, Muhammad Abduh menerapkan metode yang variatif.